Impact of firm-level attributes on listed real estate company performance. Issue 4 (24th August 2020) - Haran, Martin Edward; Lo, Daniel; McCord, Michael; Davis, Peadar; Lim, Lay Cheng
Abstract : Purpose: The purpose of this paper is to test the extent to which company-specific attributes including market capitalisation, capital structure and investment focus impact upon the performance of European listed real estate companies. Enhanced understanding of firm-level performance drivers is important for investors in order to diversify their investment portfolios and to mitigate company-specific risks at different points in the real estate cycle. Design/methodology/approach: The study centres on six key listed European real estate markets selected on the basis of market capitalisation, diversity, transparency and maturity. A series of statistical tests are undertaken using EPRA and Bloomberg data for the period of 2007–2017 using 113 listed property companies, all of whom were contemporaneous constituents of EPRA indices in this period. A series of customised performance indices were constructed to evaluate firm-level performance attributes. Findings: Firm-level attributes collectively account for more variation of risk-adjusted return than sector-level attributes over the investigation period. The impact of firm-specific attributes on performance varies significantly from country to country attributable to the contrasting cyclical property market trends in the pre– and post–Global Financial Crisis period. REITs outperformed non-REITs on a risk-adjusted basis attributed to the strong performance of "niche" market entrants allied with stronger regulatory structure. Finally, the findings showcase that sector specialist firms outperform diversified companies inferring that investors should seek to attain diversification through portfolio-based approaches rather than firm-level strategies. Practical implications: The results have implications for real estate companies aiming to raise capital internally for growth as higher return on equity in general signals reduced cost of capital. Secondly, the findings should be of practical use to multinationals specialising in international real estate trading in designing their business plans in general and formulating cross-country investment strategies in particular. Last but not least, a more refined conceptualisation of corporate-level performance drivers should complement existing professional practices in relation to business/company appraisal. Originality/value: The research integrates EPRA and Bloomberg data sets to create a series of bespoke index constructs to measure the impact of firm-specific attributes on European listed real estate companies. Additionally, the authors construct a Herfindahl Index (H.I.) to further the debate on the impacts of diversification within the listed real estate sector. This serves to further heighten investor understanding of investment allocation and portfolio optimisation strategies for the listed real estate sector given the increasingly diverse range of investment opportunities within emerging sub-markets.